Effect of somatic maturity on the aerobic and anaerobic adaptations to sprint interval training. Issue 9 (6th May 2020) - Beyer, Kyle S.; Stout, Jeffrey R.; Redd, Michael J.; Baker, Kayla M.; Church, David D.; Bergstrom, Haley C.; Hoffman, Jay R.; Fukuda, David H.
Abstract: The purpose of this study was to assess the maturity‐related differences in the aerobic and anaerobic adaptations to sprint interval training (SIT) among youth male athletes. Twenty‐seven youth male athletes were assessed for years from peak height velocity (PHV) and classified into prepubescent (PRE, n  = 7, years from PHV = −2.21 ± 0.47 years), peripubescent (PERI, n  = 10, years from PHV = 0.25 ± 0.88 years), and postpubescent (POST, n  = 10, years from PHV = 2.81 ± 0.50 years) groups based on their years from estimated peak height velocity. Participants completed a ramp exercise protocol on a cycle ergometer to determine maximal aerobic power, maximal oxygen consumption (VO2peak ), and fatigue thresholds. Following baseline, all participants completed a 4‐week SIT program that consisted of eight total training sessions. During each session, participants completed repeated 20‐s sprints on a cycle ergometer against a resistance of 7.5% of body mass. The number of sprints per sessions increased from four in session 1 to seven in session 7, with four sprints in session 8. Peak and mean power from sessions 1 and 8 were recorded. All participants completed a post‐testing ramp exercise protocol that mirrored baseline. Maximal aerobic power increased ( p  < .001) across all groups from baseline (212.61 ± 57.45 W) to post‐testing (223.24 ± 58.90 W); however, VO2peak only increased in POST (3.31 ± 0.43 to 3.54 ± 0.43 L min −1, p  = .003). Similarly, GET, VT, and RCP increased in POST, with no changes in PRE or PERI. In terms of anaerobic performance, PERI and POST had significant increases in peak and mean power. POST improved aerobic and anaerobic performance following SIT, while PERI only experienced improvements in anaerobic performance. Conversely, PRE had no changes in aerobic or anaerobic performance. The adaptations to SIT appear to be influenced by the somatic maturity status. Abstract : After 4 weeks of sprint interval training, improvements in aerobic and anaerobic exercise performance were observed in youth male athletes. However, prepubertal participants had no changes following training.